Japanese and English Students Perspective on Social Media - Fitri Alfarisy (KIRYOKU, 2021)
Social media has created new possibilities for digitally native students to engage, interact and collaborate in learning tasks that foster learning processes and the overall learning experience. By using both qualitative and quantitative data, this article discusses the perspectives of Japanese and English students towards social media. As we know, foreign language learning is facilitated by social media and especially for a new generation of students. This paper contributes to an understanding of how language learners’ perspectives on social media. 52 English students and 18 Japanese students participate in the research as the sample. We found that most of the students aware of the benefit of social media for learning languages. Furthermore, the study showed that both English and Japanese students preferred to use English or Indonesian languages to do social media activities such as posting, writing a caption, or commenting than local language or Japanese language. Therefore, Japanese and English students should improve their awareness of social media for language learners.